Effect of growth duration of Zn0.76Co0.24S interconnected nanosheets for high-performance flexible energy storage electrode materials. Issue 23 (1st December 2022) - Abbas, Nadir; Shaheen, Irum; Ali, Ijaz; Ahmad, Muhammad; Khan, Shahid Ali; Qureshi, Anjum; Niazi, Javed H.; Imran, Muhammad; Lamiel, Charmaine; Ansari, Mohd Zahid; Hussain, Iftikhar
Abstract: The direct growth of metal chalcogenides on a conductive substrate is an emerging electrode fabrication technique for high-performance supercapacitors (SCs). In this study, Zn0.76 Co0.24 S (ZCS) nanosheets were grown on carbon cloth using a direct and binder-free electrodeposition approach. The electrodeposition time was evaluated at 10 min (ZCS-10) and 15 min (ZCS-15). Both electrodes resulted in nanosheet-like morphology, with ZCS-10 consisting of compacted structures and ZCS-15 with finer structures present on the nanosheets. At 1 A g −1, the ZCS-15 electrode exhibited an enhanced specific capacity (739 C g −1 ) compared to ZCS-10 (480 C g −1 ). The network of nanosheets for the ZCS-15 electrode retained a considerable capacity of 89% after 5000 continuous charge-discharge cycles. Hence, results indicated that the fabricated ZCS electrode revealed enhancement in electrochemical properties owing to its unique nanosheet-like structures from the prolonged electrodeposition time. Graphical abstract: Image 1